The Mbokodofication of Black Women: An Autoethnographic Study of Post Dramatic Stress and the ‘Strong Black Woman' Trope - Ngcobo, Balindile (Department of Drama, 2022)
This study introduces into performance discourse the mbokodofication of Black women – that is, the production of the ‘Strong Black Woman' trope, specifically in the South African context. To this end, the study traces the genealogy of the tropes of Black womanhood that have emerged throughout the history of the South African literary canon, analyzing them critically for their varied contributions to the (mis)representations of Black women, both on stage and in the world. Employing the joint methodologies of Practice as Research and African Feminist Autoethnography (which I propose as a variant of Black Feminist Autoethnography specifically contextualized to Black African women), the study unpacks the psychological effects of mbokodofication on Black women performers who, through this phenomenon, become locked into the Sisyphean task of portraying trauma and having this trauma re-inscribed to them through the mimetic style of performance imposed by the dramatic paradigm. The ways in which the dramatic paradigm reproduces coloniality are explored and code-switching is proposed as a potential aesthetic liberator for performers who wish to obfuscate and make visible certain elements of Black womanhood from the violent colonial gaze and thus protect themselves from post-dramatic stress. The study follows the trajectory of my research enquiry and performance practice to explicate the dramaturgical process which brought into being my thesis production, Malibongwe, and, in the end, proposes the work as a post-mbokodoist manifesto.